If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -36 = -46 Reorder the terms: -36 + p = -46 Solving -36 + p = -46 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + p = -46 + 36 Combine like terms: -36 + 36 = 0 0 + p = -46 + 36 p = -46 + 36 Combine like terms: -46 + 36 = -10 p = -10 Simplifying p = -10
| -4/(7y+9)=9/(7y-4) | | 2(x-1)+3=7 | | 8x/3x+2 | | 4x+10=25-2x | | 5/6x+8/9=7/9x | | x-3*3=6 | | 5x+14x=152 | | .5x+3=4x-7 | | 4x-2=x-4 | | x^3-4x-16=0 | | 4=n(5n-9) | | x-3*0=6 | | 5=n(5n-9) | | 5n=n(5n-9) | | 13=v+5+5 | | tn=n(5n-9) | | x(x+2)=158 | | 5x+9=3x+3 | | 9x^2-54x=-69 | | x-2*3=-6 | | x-2*0=-6 | | -16x^2+22x+100=80 | | -2(7x+1)=6(1-3x)+2 | | 9=y/x | | -(3y+2)-(-2y-4)=-3 | | 4B-7=15 | | 4AB-7A=15A | | 9=x/y | | 36x^2=3600 | | a+6/3=a/2 | | Y=-3/5x+7 | | 4y-9-5y+12=0 |